1996
DOI: 10.1177/002221949602900302
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Auditory Stimulation on the Arithmetic Performance of Children with ADHD and Nondisabled Children

Abstract: This study evaluated the impact of extra-task stimulation on the academic task performance of children with attention-deficit/hyperactivity disorder (ADHD). Twenty boys with ADHD and 20 nondisabled boys worked on an arithmetic task during high stimulation (music), low stimulation (speech), and no stimulation (silence). The music "distractors" were individualized for each child, and the arithmetic problems were at each child's ability level. A significant Group x Condition interaction was found for number of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 37 publications
6
128
3
3
Order By: Relevance
“…A number of studies have found that children with ADHD benefit from extra-task distraction even if it doesn't have any informational content (Zentall & Meyer, 1987;Abikoff, Courtney, Szeibel, & Koplewicz, 1996;van Mourik, Oosterlaan, Heslenfeld, Konig, & Sergeant, 2007). These findings support the 'optimal stimulation theory' (Zentall & Zentall, 1983) which postulates that the performance of children with ADHD benefits from extra-task distraction because this increases their arousal to an optimal level.…”
Section: Asrs Scoresmentioning
confidence: 73%
“…A number of studies have found that children with ADHD benefit from extra-task distraction even if it doesn't have any informational content (Zentall & Meyer, 1987;Abikoff, Courtney, Szeibel, & Koplewicz, 1996;van Mourik, Oosterlaan, Heslenfeld, Konig, & Sergeant, 2007). These findings support the 'optimal stimulation theory' (Zentall & Zentall, 1983) which postulates that the performance of children with ADHD benefits from extra-task distraction because this increases their arousal to an optimal level.…”
Section: Asrs Scoresmentioning
confidence: 73%
“…Noise in itself can affect behavior and perception, such as performance among children with ADHD (Abikoff, Courtney, Szeibel, & Koplewicz, 1996) and solving math problems also among people who do not suffer from ADHD (Usher & Feingold, 2000).…”
Section: Ais Transactions On Human-computer Interactionmentioning
confidence: 99%
“…However, one study explored the impact of background music being played during individually administered math and vocabulary tests (Abikoff, Courtney, Szeibel, & Koplewicz, 1996).…”
Section: Settingmentioning
confidence: 99%